THE RELATIONSHIP BETWEEN SELF-COMPASSION AND FAMILY SUPPORT WITH STRESS OF INMATES IN CORRECTIONAL INSTITUTIONS CLASS II A YOGYAKARTA - Dicky Ilham Zannara; Imaduddin Hamzah (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This study aims to analyze the relationship between self-compassion and family support on the stress levels of inmates at the Class II Correctional Facility in Yogyakarta. Specifically, the research examines the impact of each variable as well as the interaction between self-compassion and family support in reducing stress. The research method employed is a quantitative approach with a correlational design. The sample consists of 150 inmates selected through purposive sampling. The instruments used include the Self-Compassion Scale, Family Support Scale, and Perceived Stress Scale (PSS). Data were analyzed using Pearson correlation tests and multiple regression to examine the relationships among the variables. The results indicate that self-compassion and family support have significant negative correlations with the stress levels of inmates. Self-compassion significantly reduces stress, whereas inmates with higher levels of self-compassion tend to experience lower stress. Similarly, family support proves to play an essential role in decreasing inmate stress. Furthermore, the interaction between self-compassion and family support shows that the combination of both has a greater impact on reducing stress levels. In conclusion, both self-compassion and family support significantly contribute to lowering the stress of inmates. Therefore, rehabilitation programs in correctional facilities should incorporate aspects of self-compassion development and strengthen family involvement to support the mental well-being of inmates.